An approach to a child with arthritis. - Talukder, Manik Kumar (Bangladesh Journal of Medicine, 2024)
Musculoskeletal and joint diseases appear to be increasing and continue to be a growing childhood health problem. Confusion over terminology and a lack of awareness of these conditions have probably contributed to their under-recognition. Musculoskeletal pain in children are common, affecting about 10-20 % of school children.2 Various local and systemic, acute and chronic, benign and malignant conditions are associated with musculoskeletal pain (Table-I). A correct diagnosis is essential for appropriate management. It is important to remember that all the limb and joint pains are not arthritis and all arthritis are not painful. A child presenting with arthritis is always a diagnostic challenge even for the most experienced clinicians. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 145-146